Dampak Penerapan Tarif Efektif Rata-Rata (TER) terhadap Beban PPh 21 Karyawan Tetap pada PT MKDF - Fadila, Amelia Nur; Susanto, Febry Fabian (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Tax revenue, particularly Article 21 Income Tax, plays a critical role in Indonesia’s fiscal sustainability but its progressive tariff system often creates complexity in payroll management and uncertainty in employees’ net salaries. To address these issues, the Ministry of Finance introduced Regulation No. 168/PMK.03/2023, which applies the Average Effective Rate (TER) as a simplified approach for calculating Article 21 Income Tax. This study aims to examine the impact of TER on the tax burden of permanent employees at PT MKDF, a medium-sized outsourcing firm. Using a descriptive quantitative design, data were collected from payroll records covering January-December 2024 and complemented with interviews from HR and finance staff. The findings show that monthly deductions remained stable at an average of IDR 924,543, but increased up to fivefold during months when bonuses or holiday allowances were paid. While TER improved payroll efficiency and reduced calculation errors, employees expressed concerns about sudden increases in tax deductions during incentive periods. This research contributes by providing empirical evidence on how TER influences the proportionality of tax burdens and administrative efficiency, complementing prior studies that focused mainly on compliance aspects. The results offer practical insights for companies in payroll management and for policymakers in evaluating the effectiveness of tax simplification reforms.